Field sampling marine plankton for biodiscovery - Ingebrigtsen, Richard Andre; Hansen, Espen; Andersen, Jeanette Hammer; Eilertsen, Hans Christian (Scientific Reports, 2017)
Source at https://doi.org/10.1038/s41598-017-15980-8 Microalgae and plankton can be a rich source of bioactivity. However, induction of secondary metabolite production in lab conditions can be difficult. One simple way of bypassing this issue is to collect biomass in the field and screen for bioactivity. Therefore, bulk net samples from three areas along the coast of northern Norway and Spitsbergen were collected, extracted and fractionated. Biomass samples from a strain of a mass-cultivated diatom Porosira glacialis were used as a reference for comparison to field samples. Screening for bioactivity was performed with 13 assays within four therapeutic areas: antibacterial, anticancer, antidiabetes and antioxidation. We analysed the metabolic profiles of the samples using high resolution - mass spectroscopy (HR-MS). Principal component analysis showed a marked difference in metabolite profiles between the field samples and the photobioreactor culture; furthermore, the number of active fractions and extent of bioactivity was different in the field compared to the photobioreactor samples. We found varying levels of bioactivity in all samples, indicating that complex marine field samples could be used to investigate bioactivities from otherwise inaccessible sources. Furthermore, we hypothesize that metabolic pathways that would otherwise been silent under controlled growth in monocultures, might have been activated in the field samples.